Synthesis and Characterization of Mn(II) Complex Compounds with Ligand Schiff Base 2-methoxy-6((4-methoxyphenylimino)methyl)phenol - Hariyanto, Nova Alfian (Proceedings of the International Conference on Green Technology; Vol 11 No 1 (2021): Proceeding of International Conference on Green Technology, 2021)
Abstract- Mn(II) complex compounds were synthesized from the reaction of MnCl 2 .4H 2 O with the Schiff base ligand 2-methoxy-6((4-methoxyphenilimino)methyl) phenol, C 15 H 15 NO 3 , by sonication method. The synthesized product has a yield of 83,24%, brownish-red solid, melting point of ~233 0 C. UV-Vis spectrum has optimum absorption at 270, 277, 335, and 615 nm. FT-IR results show absorption bands 533 cm -1 and 498 cm -1 which indicated M-O and M-N bonds. The 1 H-NMR spectrum shows one ligand indicating the presence of 5 signals with 19 protons. Powder X-ray diffraction of the Mn(II) complex shows (intensity 492 (a.u)) at 14 0 diffraction angle was observed.